Analysis of protective features of concrete in precast prestressed floor slabs (HC type) against chloride penetration - Szweda Zofia (MATEC Web of Conferences, 2018)
This paper describes protective features of concrete used in precast prestressed floor slabs against chloride penetration. HC-500 hollow core slabs are designed for constructing ceilings in skeletal buildings with reinforced concrete. Material and structural protection used in slabs determines the acceptable range of using HC slabs, taking into account durability of floors during their normal exploitation. These slabs can be used in buildings where environmental conditions affect them according to the following exposure classes: X0, XC1, XC2, XC3 (according to standards: EN 206-1: 2003 [1], EN 1992-1-1:2004 [2]). Values of diffusion coefficient for concrete collected directly from precast prestressed HC-500 slabs, were determined during short (24h and 48h) tests accelerated by the electric field. In those tests we used a thermodynamic migration model and a reverse equation of chloride migration in concrete. Taking into consideration values of diffusion coefficient and diffusion equation, the time required for chloride concentration to reach critical value for reinforcement and the thickness of reinforcement cover were established under the condition that the structure durability was subjected to the exposure class XD3 (chapter 4 of the standard PN 1992-1-1[2]).